Analisis Kesalahan Berbahasa pada Teks Eksplanasi Karangan Siswa Kelas XI MA Hasyim Asy’ari Jogoroto Tahun Pelajaran 2024/2025 - Rohani Nur Aisyah; Aida Arini; Ida Nur Hayati (Universitas Palan, 2025)
This study aims to examine Indonesian language errors in the explanatory text written by class XI students of MA Hasyim Asy'ari Jogoroto in the 2024/2025 academic year. The focus of the research, namely analyzing Indonesian language errors in the fields of phonology, morophology, syntax, and semantics This research uses descriptive qualitative research methods. The data source used is the explanatory text written by students. The research subjects were students of class XI IIS 1 MA Hasyim Asy'ari, Jogoroto. The data collection technique in the research is documentation technique. The data analysis technique in the research consists of; (1) data reduction, (2) data presentation, and (3) verification and conclusion. The results found consisted of 25 Indonesian language errors including, five phonological errors, 13 morphological errors, five syntactic errors, and two semantic errors. Phonological errors consisted of two capital letters, two punctuation marks, and one phoneme omission. Errors in morphology consist of five nonstandard word writings, two word merging errors, one non-yielding affixation writing, and five affixation writing errors. Syntax errors consisted of two redundant word usage three inappropriate diction choices, and semantic errors consisted of two findings.